Multidimensional measurement of poverty in Sub-Saharan Africa - Batana, Y (Oxford Poverty & Human Development Initiative (OPHI), 2008)
Since the seminal works of Sen, poverty is recognized as multidimensional phenomenon. Recently, there is a renewed interest in this approach since relevant databases became available. Several methods of aggregation have been suggested to measure poverty in this way. Up to now, there is no consensus on the best measure. However, a suitable measure should satisfy some useful properties. Alkire and Foster (2007) propose a multidimensional poverty measure using a counting approach. This method is applied to estimate multidimensional poverty in fourteen Sub-Saharan African countries. Poverty identification is based on four dimensions (assets, health, schooling and empowerment). The main results show important differences in poverty among the countries of the sample. The findings are compared with some standard measures such as Human Development indicators (HDI) and the income poverty among others. Comparisons show that consider additional dimensions leads to country rankings different from the standard-based rankings. Poverty is also decomposed by rural and urban location and by dimension. Rural areas are identified obviously as the poorest while schooling appear to be in general the most contributor in poverty. Finally, some robustness and sensitivity analyses are done.